Self-assembly and nanotechnology systems : design, characterization, and applications - Lee, Yoon S. (Wiley, 2012)
"Nanofabrication can be viewed as a close-to-manufacturing process for nanotechnology systems, nanoassembly is an engineering platform that backs up nanofabrication, and self-assembly is one of the core scientific principles behind nanoassembly. This book provides a systematic explanation of self-assembly, nanoassembly, and nanofabrication; it then networks them together into one book. The book is divided into four parts. The first part shows the assembly building units, and how diverse their origins and structures can be. It also presents how to analyze the building unit structures in a systematic manner. This is be called segmental analysis which is used as an underlying concept for the discussions throughout the book. The second and third parts show the designs and applications of nanotechnology systems, respectively, and how to select proper assembly principles and methods. The last part shows how to select proper characterization techniques and predictive models.This book serves as a companion book and expands on the author's previous book Self-Assembly and Nanotechnology: A Force Balance Approach by using the concepts from that book as a foundation for informatic approach to self-assembly, which can be directly expanded into nanoassembly, and into nanofabrication, which provides an effective way to design/fabricate nanofabricated systems. These topics can be used to develop a variety of nanotechnology systems effectively and efficiently, which could pave a way to green nanotechnology with its potential for economically-sound and environment-friendly nanoscale processes"--Provided by publisher.